DEVELOPMENT OF MULTIMEDIA-BASED TEACHING MATERIALS TO IMPROVE ENGLISH SPEAKING SKILLS IN JUNIOR HIGH SCHOOL STUDENTS - Latipa Femia Putri; Miken Ayu Vidiadary (PT. Intelek Cendikiawan Nusantara, 2024)
The development of multimedia-based teaching materials plays a crucial role in enhancing English speaking skills among junior high school students. This research, conducted by Miken Ayu Vidiadary and Latipa Femia Putri at STKIP Muhammadiyah Pagaralam, investigates the effectiveness of multimedia as a teaching tool. The study highlights the influence of advances in science and technology on education, particularly the integration of information technology into learning environments. Middle school students often face challenges such as shyness, lack of confidence, and pronunciation difficulties when learning English. Multimedia-based teaching materials address these issues by creating engaging and supportive learning environments. Using a qualitative approach that includes case studies, observations, interviews, and document analysis, the research demonstrates that multimedia enhances student retention and comprehension. The findings emphasize the benefits of multimedia in education, showing that it facilitates interaction between teachers and students, increases motivation, and provides consistent, repeatable learning experiences. Consequently, multimedia-based teaching materials are shown to be effective in improving English speaking skills among junior high school students.